Evolutionarily distinct bacteriophage endolysins featuring conserved peptidoglycan cleavage sites protect mice from MRSA infection. (27th January 2015) - Schmelcher, Mathias; Shen, Yang; Nelson, Daniel C.; Eugster, Marcel R.; Eichenseher, Fritz; Hanke, Daniela C.; Loessner, Martin J.; Dong, Shengli; Pritchard, David G.; Lee, Jean C.; Becker, Stephen C.; Foster-Frey, Juli; et al.
Abstract: Objectives: In the light of increasing drug resistance in Staphylococcus aureus, bacteriophage endolysins [peptidoglycan hydrolases (PGHs)] have been suggested as promising antimicrobial agents. The aim of this study was to determine the antimicrobial activity of nine enzymes representing unique homology groups within a diverse class of staphylococcal PGHs. Methods: PGHs were recombinantly expressed, purified and tested for staphylolytic activity in multiple in vitro assays (zymogram, turbidity reduction assay and plate lysis) and against a comprehensive set of strains ( S. aureus and CoNS). PGH cut sites in the staphylococcal peptidoglycan were determined by biochemical assays (Park–Johnson and Ghuysen procedures) and MS analysis. The enzymes were tested for their ability to eradicate static S. aureus biofilms and compared for their efficacy against systemic MRSA infection in a mouse model. Results: Despite similar modular architectures and unexpectedly conserved cleavage sites in the peptidoglycan (conferred by evolutionarily divergent catalytic domains), the enzymes displayed varying degrees of in vitro lytic activity against numerous staphylococcal strains, including cell surface mutants and drug-resistant strains, and proved effective against static biofilms. In a mouse model of systemic MRSA infection, six PGHs provided 100% protection from death, with animals being free of clinical signs at the end of the experiment. Conclusions: Our results corroborate the high potential of PGHs for treatment of S. aureus infections and reveal unique antimicrobial and biochemical properties of the different enzymes, suggesting a high diversity of potential applications despite highly conserved peptidoglycan target sites.